Flood estimation and river analysis of Sungai Isap - Muhammad Hazwan, Hussin (2010)
The purpose of this paper was to expose the people about the flood occurrences in Kuantan in the past few years and to analyse the rainfall and river cross section data to estimate the next flood event as well as studying the river behaviours and properties. This study was carried out due to the flood event that occurred in the Kuantan city during the monsoon period. Heavy rainfall occurres every year and often causes flooding problem in Kuantan city due to the. overflow from Sungai Lembing and Kampung Panching. Although flood is difficult to avoid, we still can forecast the flood and take some precautions. Infoworks Wallingford Software was used in order to estimate the flood events by analysing the design rainfall produced from actual rainfall data for the past few years (2009) during September to March which acquired from Department of Irrigation Drainage (DID) and the current river cross-section data, which acquired from private company, site survey and Google Earth. This study gave the results of flood occurrence on 100 years AR! and the suitable solution was proposed.